The 2nd Meeting of European Committee for standardization: project committee for Halal food - Kayadibi, Saim; Usta, Ramazan (Mehir Vakfi, 2014)
The Halal Industry is the fastest growing global business across the world although it is a new growing sector. Due to its hygienic, good quality, wholesome and contamination free principles it is a highly demanded emerging market force attracting not only Muslims but also non-Muslims around the world. Currently the halal food industry is estimated at USD 600 billion per year; nevertheless, the experts on halal food foresee that it may reach up to USD 2.1 trillion in the following years. In responds to the demand of people towards halal food, the halal food requirements and its industry must be standardized in order to produce good quality, clean, genuine, and safe halal products.